2011
DOI: 10.1007/s10763-011-9297-9
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Students’ Conceptual Understanding of Plant Defense Responses Using the Fighting Plant Learning Unit (Fplu)

Abstract: Most students think animals are more interesting than plants as a study topic believing that plants are inferior to animals because they are passive and unable to respond to external challenges, particularly biological invaders such as microorganisms and insect herbivores. The purpose of this study was to develop an inquiry-based learning unit, the Fighting Plant Learning Unit (FPLU), which focuses on plant defense responses to biological stimuli. The study also investigated students' perceptions of the FPLU i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 68 publications
1
2
0
4
Order By: Relevance
“…For example, students believe that, unlike animals, plants do not feed, move, communicate, react to stimuli, etc (Hoekstra 2000;Wandersee and Schussler 1999). The data from these studies correspond with our preliminary research findings with Thai high-school students (Nantawanit et al 2009). According to our study, most students believe that plants cannot respond to stimuli, particularly stimuli generated by microorganisms and insects; this view partially explains why students are unenthusiastic about studying plants.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…For example, students believe that, unlike animals, plants do not feed, move, communicate, react to stimuli, etc (Hoekstra 2000;Wandersee and Schussler 1999). The data from these studies correspond with our preliminary research findings with Thai high-school students (Nantawanit et al 2009). According to our study, most students believe that plants cannot respond to stimuli, particularly stimuli generated by microorganisms and insects; this view partially explains why students are unenthusiastic about studying plants.…”
Section: Introductionsupporting
confidence: 84%
“…In this paper, we propose a simple hands-on experiment, which is an activity of the Fighting Plant Learning Module (FPLM) developed by the authors (Nantawanit et al 2009). In this activity, high-school students investigate how a plant organ (red chilli fruit) responds to invading microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…After following the defined steps above, a researcher should follow some other steps explained in the next steps to create the second tier (justification) of the two-tier tests, which makes two-tier tests different from other tests. In order to determine the misconceptions which are used as alternatives or causes of the second tier, it was found that in some studies, only literature review (Cheang et al, 2015;Moutinho et al, 2016); in some studies, interviews with students (Chiu, 2007;Dahsah & Coll, 2008;Lee, 2007;Lin, 2004;Monteiro et al, 2012;; and in some studies both interviews with students and literature review on the misconceptions about corresponding topics of the study (Adadan & Savaşçı, 2012;Chang et al, 2007;Chang et al, 2010;Eymur & Geban, 2017;Kao, 2007;Nantawanit et al, 2012;Othman et al, 2008;Taber & Tan, 2007;Treagust, 1988;Treagust et al, 2010;Tsai et al, 2007;Tsiu & Treagust, 2010;Sia et al, 2011;Wang, 2004;Yen et al, 2004;Yen et al, 2007) are followed by the researchers. As a result of detailed examinations, the researchers of the present study propose that to create alternatives to the second tier of two-tier tests, researchers should conduct both literature review and interviews with students to determine all the misconceptions about corresponding topics as much as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Todavia, o processo de ensino-aprendizagem em Botânica muitas vezes é considerado um tema incipiente e entediante (Nantawanit et al, 2012;Buckeridge, 2016), demonstrando precariedade do ensino. Parte deste problema é atribuído à falta de estrutura física e material nas escolas para as aulas, bem como pela dificuldade de professores elaborarem aulas que proporcionem maior interesse aos alunos.…”
Section: Introductionunclassified
“…Mas os sintomas atribuídos são os mesmos: como a não percepção das plantas no cotidiano, a visão de que as plantas são apenas cenários para a vida animal, a negligência da importância das plantas e a insensibilidade das características estéticas das plantas. Também compreende falta de disposição de apreciar as plantas, seja pela sua aparência ou pela falta de importância biológica que elas possuem para a natureza, tornando-as inferiores na visão humana, passivas (Nantawanit et al, 2012) e insensíveis (Gagliano, 2013). E quanto menor o interesse pela Botânica, maior é o déficit de conhecimento no tema e com ele podese perder o hábito de práticas ambientais no futuro (Krosnick et al, 2018).…”
Section: Introductionunclassified